Enhancing navigation safety through the Nile River to avoid bottlenecks using a quasi-real-time approach and Google Maps - Yousra Salem; Shenouda Bakhiet; Wael Khedr (JES: Journal of Engineering Sciences, 2024)
The great importance of the Nile River emerges from the fact that it represents the main water source for Egypt and its being an important water path for sailing or for Nile tourism cruises. Because of climate change and the construction of the Ethiopian Renaissance Dam, Egypt may have to reduce the discharges from the High Aswan Dam (HAD), which may cause a reduction in water depth below a safe level for navigation. Consequently, this study aims to present a quasi-real-time approach to detect the locations of bottlenecks that threat navigation path via mobile Google Maps. Accordingly, the topographic, hydraulic data, the alignment and geometry of the navigational channel, were collected from the Ministry of Water Resources and Irrigation of Egypt. AutoCAD Civil 3d is adopted in this study to determine navigational bottleneck locations of the Nile River's first reach. Two surface models were created: The Riverbed surface and the navigational path surface using a Triangular Irregular Network (TIN). As a result of the created TIN-Surface modelling ; the amount of sediment, that should be dredged, was estimated (at about 2.1 million.m3). In addition, the navigation path bottlenecks map for the studied reach was created based on minimum water levels at Aswan High Dam's winter closure and the navigational path's geometry. In conclusion, this study provides a simple solution for avoiding bottlenecks by presenting a user-friendly web Google Maps of these locations to represent the Nile River's current navigation condition in quasi-real-time and support the decision-maker on river navigation conditions.